2019
DOI: 10.1126/sciadv.aaw6127
|View full text |Cite
|
Sign up to set email alerts
|

The essential role of the transporter ABCG2 in the pathophysiology of erythropoietic protoporphyria

Abstract: Erythropoietic protoporphyria (EPP) is an inherited disease caused by loss-of-function mutations of ferrochelatase, an enzyme in the heme biosynthesis pathway that converts protoporphyrin IX (PPIX) into heme. PPIX accumulation in patients with EPP leads to phototoxicity and hepatotoxicity, and there is no cure. Here, we demonstrated that the PPIX efflux transporter ABCG2 (also called BCRP) determines EPP-associated phototoxicity and hepatotoxicity. We found that ABCG2 deficiency decreases PPIX distribution to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Subsequently, the resulting mixture was centrifuged at 15,000 rpm for 10 min. PPIX in mouse liver was extracted according to a previous report (Wang et al, 2019). Briefly, 50 mg of liver sample was homogenized in 250 μL of water, and the resulting 100 μL of suspension was mixed with 200 μL of methanol/acetonitrile (1:1, v/v) followed by centrifugation at 15,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the resulting mixture was centrifuged at 15,000 rpm for 10 min. PPIX in mouse liver was extracted according to a previous report (Wang et al, 2019). Briefly, 50 mg of liver sample was homogenized in 250 μL of water, and the resulting 100 μL of suspension was mixed with 200 μL of methanol/acetonitrile (1:1, v/v) followed by centrifugation at 15,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The mobile phases for metabolite analysis were A (0.1% formic acid in water) and B (0.1% formic acid in acetonitrile), and were delivered at a flow rate of 0.5 mL/min with a gradient elution (0.0-1.0 min, 2% B; 1.0-12.0 min, 2-95% B; 12.0-20.0 min, 95% B; 20.0-20.5 min, 95-2% B; 20.5-24 min, 2% B). PPIX assay was conducted using a previously reported method (Wang et al, 2019). In brief, PPIX analysis was performed on an Acquity UPLC BEH C18 column (2.1 × 50 mm, 1.7 µm) and acetonitrile/water containing 2 mM ammonium bicarbonate and 0.05% aqueous ammonia was used as the mobile phase.…”
Section: Methodsmentioning
confidence: 99%
“…The physiological role of ABCG2 in red blood cells and stem cells is enigmatic to some extent. Since phototoxic porphyrins, such as the plant-derived pheophoride A and the heme precursor protoporphyrin IX (PPIX), are noted substrates of ABCG2, its expression in the erythroid precursor cells and in mature RBCs may indicate its involvement in heme metabolism [ 50 , 67 , 68 ]. It is worth noting, however, that numerous membrane proteins without known function in RBCs are present in their membrane, i.e., the sterol transporter ABCA1 ( , accessed on 9 February 2021) [ 69 , 70 ].…”
Section: The Physiological Functions Of Abcg2 and Its Role In Mulmentioning
confidence: 99%
“…Accumulation of PPIX in EPP patients causes hepatotoxicity and phototoxicity primarily in the skin. A recent study elegantly demonstrated that Abcg2-deficency prevents mice from EPP-associated phototoxicity and hepatotoxicity by altering the disposition of PPIX [ 68 ]. In this case, this phototoxin is mostly retained in the RBCs, thus causing a reduced plasma level and preventing PPIX accumulation in the skin and the liver/bile.…”
Section: Medical Conditions Associated With Abcg2 Mutations and Pomentioning
confidence: 99%
“…Intriguingly, there are no reports of light‐induced pathologies of individuals with the junior blood group, which typically shows a loss of ABCG2 surface expression in erythrocytes [76]. Of note, animal models of erythropoietic protoporphyria suggest a role for ABCG2 in cytoprotective porphyrin transport [77], mirroring a likely protective role for ABCG2 as a physiological porphyrin transporter in hematopoietic stem cells [78]. With its broad substrate specificity, other definitive physiologically relevant substrates and/or metabolites of ABCG2 remain to be identified.…”
Section: Discovery and Biology Of Abcg5 And Abcg8mentioning
confidence: 99%